DORMANT PERIOD OF PEAR VARIETIES IN THE CHUI VALLEY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The study was carried out in the conditions of the Research Institute of the BotanicalGarden. E. Gareeva. The objects of study are collection varieties introduced from different regions.The purpose of the research is to establish the dormant period of pear varieties in the Chui valley.To determine the timing of the release of the kidneys from the state of dormancy, the method ofcut branches was used. The results of the timing of the release of pear fruit buds from dormancyare presented. Varieties with a long dormant period have been identified.
Keywords: introduction, pear cultivars, dormancy period, dormancy depth, timing of exit from dormancy, duration of dormancy period, winter hardiness, fruit bud.